Wealth management : private banking, investment decisions and structured financial products - Chorafas, Dimitris N. (Elsevier/Butterworth-Heinemann, 2006)
This book has two themes: Private Banking and investment decisions regarding Structural Financial Products. Dr. Dimitris Chorafas examines in a rigorous way whether structured financial products are advisable investments for retail and institutional investors and, if yes, which risks they entail. As our society becomes increasingly affluent, and state-supported pension schemes find it difficult to survive, a growing number of high net-worth individuals, and families, have become retail investors looking for ways and means to optimize wealth management, and Private Banking deals with these sorts of clients. Private banking also deals with clients that are institutional investors, such as pension funds, mutual funds, and insurance companies, as well as not-for-profits, foundations and companies explicitly set up for wealth management. Both institutional and retail investors are being offered by the banks they work with structured products. Typically, these are securities that provide them with a redemption amount, with may be either with full or partial capital protection, and some type of return. The book examines structured financial products, their polyvalent nature, and the results which could be expected from them. Return on structural instruments, which are essentially derivatives, is paid in function of a specific investment strategy on selected underlying asset(s). This essentially means on the performance of the underlyings, obtained by asset managers, which may be banks or hedge funds, through purchase or sale of embedded options. But there are risks. Both risk and return from structured products are related to three main issues: the volatility of future value of an underlying, the uncertainty of future events, and the exposure of the product. Every type of investment is subject to market forces, and the more leveraged a portfolio is, the greater will probably be both the assumed risk and the expected reward. The fact that structured financial products appeal, or at least are being marketed, to both retail investors and institutional investors makes the dual approach deliberately chosen in this book most advisable. This book addresses all these issues in a practical manner with numerous case studies and real-world examples drawn from the authors intensive research. *Because it is based on intensive research, the book is rich in practical examples and case studies *Addresses the growing trend towards the use of structured financial instruments in private banking *Thorough treatment of structured financial products that keeps maths to a minimum.